English | Español

# Try our Free Online Math Solver! Online Math Solver

 Depdendent Variable

 Number of equations to solve: 23456789
 Equ. #1:
 Equ. #2:

 Equ. #3:

 Equ. #4:

 Equ. #5:

 Equ. #6:

 Equ. #7:

 Equ. #8:

 Equ. #9:

 Solve for:

 Dependent Variable

 Number of inequalities to solve: 23456789
 Ineq. #1:
 Ineq. #2:

 Ineq. #3:

 Ineq. #4:

 Ineq. #5:

 Ineq. #6:

 Ineq. #7:

 Ineq. #8:

 Ineq. #9:

 Solve for:

 Please use this form if you would like to have this math solver on your website, free of charge. Name: Email: Your Website: Msg:

# Functions and Inverse Functions

Asterisks denote definitions which are not in the textbook.

1. We review the definitions leading up to the textbook's definition of inverse function.

(a) *A relation is a set of ordered pairs .

(b) If there are sets R, A, and B such that

R ⊆ A × B,

then R is said to be a relation between A and B.
(Clearly, if R is a relation between A and B, then R is a relation as defined in (a).)

(c) *The domain of a relation R, denoted by dom(R), is defined by (d) *A relation R is called a function, or is said to have the function property , iff
∀ a, b, c, and d, if (a, b) ∈ R and (c, d) ∈ R and a = c, then b = d.

In other words, a relation R is a function iff
if (a, b) ∈ R and (a, d) ∈ R then b = d.

(e) Given sets A and B, a relation F is said to be a function from A to B iff

F is a relation between A and B;
F has the function property ;
dom(F ) = A (note that the fact that F is a relation between A and B implies that ran(F) ⊆ B ).

The notation F : A → B means that F is a function from A to B, although the exact verbal
interpretation of the symbols F : A → B may differ slightly depending on the context.

(f) Theorem. *For a function F : A → B, define the relation F-1 by
(I) (b, a) ∈ F-1 iff (a, b) ∈ F , (I)
(i.e.,
z ∈ F-1 iff ∃ a, b z = (b, a) and (a, b) ∈ F )

If the function F : A → B is bijective, then F -1 is a function from B to A. (You should be
able to prove this.)

(g) The definition of inverse function given in the textbook can be expressed in the following way:
If a function F : A → B is bijective, then the function F-1: B → A defined above is called the
inverse function of F : A → B.

*To distinguish this concept from another inverse function concept discussed below, we will
temporarily refer to this as the L-inverse function of F : A → B.
(The letter “L” refers to the author of the textbook.)

*I.e., a function G : B → A is the L-inverse function of a bijective function F : A → B iff
dom(G) = B and G is the inverse relation F-1 of the relation F as defined in (I) above.

(h) *Expressed in standard function notation instead of with the use of ordered pairs , equation (I)
above gives the following defining condition for the L-inverse:
For every a in A and b in B ,

(I') F-1(b) = a iff F(a) = b.

We will give another definition of “inverse function”, and then we will comment on the definitions and
the relationships between them.

2. *Given a function f : A → B, a function g : B → A is called an inverse of the function f : A → B
iff
∀ x in A, g (f (x)) = x,
and
∀ y in B, f (g (y)) = y.

We will temporarily refer to such a function g : B → A as an algebraic -inverse function of
f : A → B .

It should be clear that this definition is equivalent to the following :

For any set S, let idS denote the identity function on S.

Given a function f : A → B, a function g : B → A is called an ( algebraic -)inverse of the
function f : A → B iff

g o f = idA
and
f o g = idB .

Uniqueness. It is clear that the L-inverse of a function is unique, if it exists, since the L-inverse
function is obtained in a particular way from the original function. On the other hand, if the inverse
function is defined as an algebraic -inverse, then it has to be proved that if such an inverse function
exists, then it is unique.

Equivalence of L- inverse and algebraic -inverse. You should be able to prove (this is related to
Ex. 7.29 in the textbook) that the L-inverse idea and the algebraic -inverse idea are equivalent in the
following
sense:

A function f : A → B has an algebraic -inverse function iff f : A → B is bijective.

A function g : B → A is the L-inverse function of f : A → B iff g : B → A is an algebraic -inverse

function of f : A → B.

Uniqueness.
Note that this implies that if an algebraic-inverse function exists, then it is unique.

 Prev Next